Ecological – Hygienic assessment of Health status the Aral Sea Region (Eurasian Journal of Ecology, 2018)
Given the forecast assessment of the development of ecological-hygienic situation and health status of the population of the Aral sea region.When studying the health status of the population of the Aral sea in suchnosological forms of diseases like hypertension, cholelithiasis, gastric ulcerdisease show the importance of the salt composition of water in the etiopathogenesis of these diseases.The results revealed that the use of waterwith high mineralizovannaja and rigidity, a high content of a number ofcomponents in the salt composition leads to various physiological changes, especially in the hot and arid climate of the region. As well as increasedwater salinity significantly violates the specific functions of the femalebody. Revealed more frequent disturbance of ovarian function accordingto the type hypermenstrual syndrome (3 times), significantly decreased thenumber of pregnancies, 2 times increase in spontaneous miscarriages andother disorders of pregnancy (toxicosis, nephropathy).Key words: drinking water, correlation, human ecology, maximumpermissible concentration, forecasting.